Model Pembelajaran Kooperatif Tipe Two Stay Two Stray untuk Meningkatkan Keterampilan Menyimak Kelas V di SDN 1 Mantup - Afriska Anggi Putri Vianto; Mochammad Mifthacul Huda; Ahmad Ipmawan Kharisma (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Listening skills are one of the essential language skills that elementary school students need to master because they support the success of the learning process. Based on the preliminary observation conducted in Grade V of SDN 1 Mantup, students’ listening skills were still relatively low, indicating the need for improvement through the implementation of an instructional model that actively engages students in learning activities. This study aimed to improve the listening skills of Grade V students at SDN 1 Mantup through the implementation of the Two Stay Two Stray (TSTS) cooperative learning model. This research employed Classroom Action Research (CAR), which was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants of this study were 30 Grade V students of SDN 1 Mantup. Data were collected through observation, tests, and documentation. The findings revealed that the implementation of the Two Stay Two Stray cooperative learning model successfully improved students’ listening skills. Learning mastery increased from 53% in Cycle I to 93% in Cycle II. Teacher activity improved from 53% to 93%, while student activity increased from 61.25% to 91.25%. The improvement occurred because the Two Stay Two Stray model provided students with opportunities to discuss, exchange information, listen to the results of other groups’ discussions, and convey the information obtained to their original groups. Therefore, the Two Stay Two Stray cooperative learning model is considered effective in improving the listening skills of Grade V students at SDN 1 Mantup.